Teaching English towards the Hearing-Impaired Students - Antonius Setiawan (Journal of English Language Teaching and Islamic Integration, 2020)
The EFL teaching is challenging. Moreover, teaching English towards the hearing-impaired students (hereafter HIS) must have its own uniqueness because of the greater challenges. The exploration in this phenomenological study goes with the teacher’s lived experience in teaching English especially vocabulary towards the HIS. Telling narratively of the teacher’s lived experience in teaching English towards the HIS is the purpose of this research. The descriptions go on the teacher’s understanding, belief, feeling, intention, and action which are elaborated by the purpose of the teaching, the materials, the technique, and the achievement. According to the findings, the purposes of teaching vocabulary are to enrich their vocabulary mastery and to proof that the HIS can learn language. The teacher can only teach simple words because it takes time and lots of efforts. Visualization is the best teaching technique ever for the HIS because it helps better memorization since it gives emotional feeling for them. In conclusion, the HIS can learn simple vocabulary. Visualization helps them memorizing words better.